Factors related to willingness to participate in biomedical research on neglected tropical diseases: A systematic review - Raimundo-Silva, Vinícius; Marques, Caio Torres; Fonseca, João Rezende; Martínez-Silveira, Martha Silvia; Reis, Mitermayer Galvão (PLoS neglected tropical diseases, 2024)
Understanding the barriers to and facilitators of participation in research could enhance recruitment rates for biomedical research on Neglected Tropical Diseases (NTDs) and help to avoid the problems associated with poor recruitment. We conducted a systematic review to identify factors related to willingness to participate in biomedical research on Neglected Tropical Diseases (NTDs). Our search included the following databases: Medline/PubMed, Embase (Embase.com), Global Index Medicus (WHO), Web of Science (Core collection), and gray literature. We included studies that analyzed or reported factors associated with willingness to participate in NTD research, using either quantitative methods (such as clinical trials, cohorts, and cross-sectional studies) or qualitative methods (such as focus group discussions, semi-structured interviews, and in-depth interviews). There were no language restrictions, but we excluded review articles, notes, case reports, letters to the editor, editor's notes, extended abstracts, proceedings, patents, editorials, and other editorial materials. Screening of citations, data extraction, and risk of bias assessment was conducted by independent reviewers, according to the study protocol registered on PROSPERO. For analyses, we assessed the frequency of barriers, enablers, and the frequency of recruitment interventions mentioned in the included studies. The protocol for this systematic review was registered under registration number CRD42020212536. (S1 Appendix) We identified 2070 citations, 1470 from the databases, and 600 from other sources. From those, eleven studies were selected for data extraction and analysis. The studies were conducted in Africa, Asia, and North America. Personal health benefits, monetary benefits, and community engagement and sensitization strategies were identified as the main reasons for participating in biomedical research on Neglected Tropical Diseases (NTDs). However, distrust in researchers, lack of knowledge about research methods among potential participants, and previous negative experiences were identified as the main barriers to participating in biomedical research on NTDs. This systematic review provides recommendations for improving adherence to biomedical research on Neglected Tropical Diseases, which can be applied in practice.